Magdalene Instagram Followers Interactivity on Gender Equality Issues (Virtual Ethnography Study on Instagram Followers @magdaleneid in #komikceritaindah content) - Dinan Abshari Ekantoro; Alila Pramiyanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Gender inequality is still common in Indonesia. The Women Lead digital campaign organized by Magdalene with Investing in Women to raise public awareness about gender equality in the workplace. #komikceritaindah is content that covers cases of gender equality in the workplace with comic illustrations. The audience has an opinion on the issue of gender equality that often occurs in #komikceritaindah. The majority of the audience shared their personal experiences related to the issue of gender equality. Therefore, researchers are interested in analyzing more deeply the interactivity of the issue of gender equality discussed by followers of @magdaleneid in the #komikceritaindah content. This study focuses on interactivity that discusses the issue of inequality in #komikceritaindah content for the period August to December 2022. Researchers use a qualitative approach with virtual ethnographic study methods in order to be able to analyze in depth audience activities that occur online and their relationship with offline conditions. This study collects data by using social media observation methods and interviews with informants. This research refers to the interactivity theory of Mc Millan and Dowes in 2000 about the dimensions of interactivity in cyber media. As a result, the six dimensions of interactivity, namely direct of communication, time flexibility, senses of place, level of control, responsiveness, perceived purpose of communication, occur in interactions when discussing gender issues in #komikceritaindah.